An Optimal Scheduling Strategy for Integrated Energy Systems Using Demand Response - Lin, Shunfu; Lin, Mengchen; Shen, Yunwei; Li, Dongdong (Frontiers in Energy Research, 2022)
With the development of power-to-gas (P2G) technology and demand-response (DR) technology, new ideas have been proposed for research into the scheduling strategy for integrated energy systems (IER). Focusing on wind power consumption, this paper proposes a day-ahead scheduling strategy for IER with P2G equipment, taking into consideration DR. On the energy consumption side, a demand elasticity matrix is introduced to describe the user’s participation in DR. On the energy supply side, P2G equipment is introduced to improve the coupling of electricity and natural gas, and scenario generation and reduction techniques are introduced to describe the uncertainty of renewable energy output. The maximum net income of the IER is set as the objective function. The optimal scheduling scheme of the system was obtained by solving the scheduling model. The results indicate that the proposed strategy outperforms the traditional operation and can achieve peak cutting and valley filling, maximize the net income of the IER operators, promote the consumption of renewable energy and improve the energy utilization rate of the system.